Time models for the classification and identification of production events - Dangelmaier, Wilhelm (Megatrend digitization - potentials of work and company organization)

How to Complete Customer Requirements Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB 2016))

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia Charlotte; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts)

Ein Verfahren zur simulationsgestützten Optimierung von Einrichtungsparametern an Werkzeugmaschinen in Cloud-Umgebungen - Laroque, Christoph; Weber, Jens; Reisch, Raphael-Elias; Schröder, Christian (Nissen, Volker;Stelzer, Dirk;Straßburger, Steffen;Fischer, Daniel (Hrsg.): Multikonferenz Wirtschaftsinformatik (MKWI) 2016)

Multi-criteria scheduling and control in dynamic and stochastic environments: A contribution to the creation of robust schedules for freight handling in air freight terminals - Boxnick, Simon

Intelligent work preparation in the cloud - Rehage, Gerald; Isenberg, Florian; Reisch, Raphael-Elias; Weber, Jens; Jurke, Benjamin; Pruschek, Peter (wt workshop technology online)

A Metric for Candidate Selection for a Robust Opportunistic Container Routing in high Complex Distribution Centers - Kopecki, Lukas

A Technical Approach of a Simulation-Based Optimization Platform for Setup-Preparation via Virtual Tooling by Testing the Optimization of Zero Point Positions in CNC-Applications - Weber, Jens (Proceedings of the 2015 Winter Simulation Conference)

A Comparison of the Usage of Different Approaches for the Management of Plant Engineering Projects - Akbulut, Akin; Laroque, Christoph; Wenzel, Sigrid; Jessen, Ulrich (Proceedings of the 2015 Winter Simulation Conference)
Customized planning, engineering and construction of one-of-a-kind products (like wind energy, biogas or power plants) are complex and contain a lot of risks and temporal uncertainties, e.g. of logistics and project schedules. Therefore the management of this kind of projects has to be supported by adequate methods for the estimation of project risks and uncertainties. Based on the results of the joint research project simject of the Universities of Paderborn and Kassel, which aims at the development of a demonstrator for simulation-based and logistic-integrated project planning and scheduling, this paper discusses the usage of different approaches for supporting project management of plant engineering projects. After a short introduction and description of the approaches to be compared a wind energy plant as evaluation model as well as the application of the different methods are presented. Additionally, the usage of the approaches is compared and the advantages and disadvantages are pointed out.

A Deadlock-Free Route Reservation Method for Automatized Decentralized Controlled Transportation in High Complex Distribution Centers - Kopecki, Lukas